Handling of Imported Household Furnishings from China which Caught Intelligence Result Notes - Azis, Rizal Abdul; Utami, Eva Yuniarti (Eastasouth Institute, 2024)
This research aims to investigate the handling of the Intelligence Result Note (NHI) case regarding imports of household furniture from China at PT. Ngupit Asasta Logistik. This research uses a qualitative descriptive approach with triangulation analysis. Primary data was obtained through interviews, observation, and documentation, while secondary data came from relevant literature sources. The results show that imports of household furniture from China are subject to NHI and are suspected of violating the traffic law so imported goods are blocked by Customs and Excise officials in the customs area. The obstacles faced are costs, time, and energy. The results of the research carried out provide recommendations for enforcing company SOPs in resolving NHI as well as developing special SOP for handling imports affected by NHI at PT. Ngupit Asasta Logistik.